Dysregulation of immune response in PCOS organ system - Wang, Jingxuan; Yin, Tailang; Liu, Su (Frontiers in Immunology, 2023)
Polycystic ovary syndrome (PCOS) is the most common reproductive endocrine disorder affecting women, which can lead to infertility. Infertility, obesity, hirsutism, acne, and irregular menstruation are just a few of the issues that PCOS can be linked to. PCOS has a complicated pathophysiology and a range of clinical symptoms. Chronic low-grade inflammation is one of the features of PCOS. The inflammatory environment involves immune and metabolic disturbances. Numerous organ systems across the body, in addition to the female reproductive system, have been affected by the pathogenic role of immunological dysregulation in PCOS in recent years. Insulin resistance and hyperandrogenism are associated with immune cell dysfunction and cytokine imbalance. More importantly, obesity is also involved in immune dysfunction in PCOS, leading to an inflammatory environment in women with PCOS. Hormone, obesity, and metabolic interactions contribute to the pathogenesis of PCOS. Hormone imbalance may also contribute to the development of autoimmune diseases. The aim of this review is to summarize the pathophysiological role of immune dysregulation in various organ systems of PCOS patients and provide new ideas for systemic treatment of PCOS in the future.